Security of tenure and access to finance by resettled smallholder farmers in Zimbabwe - Chrispen , Maireva (Turisztikai és Vidékfejlesztési Tanulmányok, 2023)
Post the fast-track land reform programme, the Government of Zimbabwe came up with the A1 settlement permit to assure resettled farmers of security of tenure on the land. The resettled farmers need finance to be productive on the farms they occupy. This study was carried out to evaluate the effect of the A1 settlement permit on the ability of smallholder farmers to access finance from formal financial institutions using a qualitative phenomenological design. Fifteen interviews were conducted to collect data from the resettled farmers. The research found that most of the smallholder farmers did not have access to finance from formal financial institutions as they were excluded from formal financial markets. It was also found that most formal financial institutions shunned A1 settlement permits as security of tenure documents, as they believed that the permits were not bankable. The study also found that some scrupulous and unscrupulous financial services providers provide finance to smallholder farmers. The study recommended that access to finance is paramount if the smallholder farmers are to fully utilise their allocated pieces of land. Further, robust financial education and literacy must be encouraged so that there is increased access to finance by smallholder farmers.